Modeling tension-compression asymmetry and failure anisotropy in bending operations of a magnesium alloy. Issue 1 (1st May 2022) - Steglich, D; Besson, J
Abstract: The deformation behavior of the magnesium sheet alloy AZ31 at room temperature is investigated using different standard and non-standard mechanical tests as well as respective finite-element simulations. In order to address the bendability, three-point bending tests were performed for different orientations of the sample with respect to the sheets axes of orthotropy. The elastic-plastic deformation was modeled using a two-yield-surface model, which is able to describe the evolving strength differential effect as well as the anisotropy of the material. For the prediction of material failure, a numerically efficient damage criterion based on transformation of strain rates is calibrated and applied. It is shown that this model is able to predict the observed edge failure of specimens with good accuracy.